1988
DOI: 10.1051/rnd:19880608
|View full text |Cite
|
Sign up to set email alerts
|

Biliary and pancreatic secretory component of the migrating myoelectric complex in the pig. Effect on intraduodenal pH

Abstract: Summary. The aim of the present study in the pig was to describe the biliary and pancreatic secretory component of the migrating myoelectric complex (MMC) during the interdigestive period and after feeding, and to examine the effects of the extracorporal diversion of biliary or pancreatic secretions on the MMC and on the cyclical variation of intraduodenal pH.In a first trial six pigs (50.6 ± 1 .6 kg) were fitted with a permanent catheter in the common bile duct (3 pigs) or in the pancreatic duct (3 pigs) to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Recent studies have revealed that pancreatic secretion in preruminant calves is periodic (Zabielski et al 1993;Zabielski, 1994). This pattern is to some extent similar to the periodic pancreatic secretion (PPS) observed in dogs (Boldyreff, 191 1;Magee & Naruse, 1983;Konturek et al 1986), pigs (Abello et al 1988;Kiela et al 1996), rats (Onaga et al 1993) and human subjects (Vantrappen et al 1979). It is manifested by cyclically recurring fluctuations in the secretion of pancreatic juice concomitant with the migrating myoelectric complex (MMC) of the duodenum.…”
supporting
confidence: 62%
“…Recent studies have revealed that pancreatic secretion in preruminant calves is periodic (Zabielski et al 1993;Zabielski, 1994). This pattern is to some extent similar to the periodic pancreatic secretion (PPS) observed in dogs (Boldyreff, 191 1;Magee & Naruse, 1983;Konturek et al 1986), pigs (Abello et al 1988;Kiela et al 1996), rats (Onaga et al 1993) and human subjects (Vantrappen et al 1979). It is manifested by cyclically recurring fluctuations in the secretion of pancreatic juice concomitant with the migrating myoelectric complex (MMC) of the duodenum.…”
supporting
confidence: 62%
“…Further experiments led us to conclude that a true biliary and pancreatic secretory component of MMC exists in the pig [2]. Bile secretion is always minimal during duodenal quiescence, and increases after the start of the ISA phase to reach a maximum at the beginning of the RSA phase, i.e.…”
Section: Motor and Secretory Coordination In The Gastroduodenal Areamentioning
confidence: 86%
“…min -1 ) at the onset of the RSA phase. However, the major role of the gastric acid outflow to determine the cyclical variation of intraduodenal pH, and the role of bile and pancreatic secretions in the neutralisation of the duodenal chyme were simultaneously confirmed, as the cyclical variation of pH took place within a much more acid range during biliary and pancreatic diversion [2].…”
Section: Motor and Secretory Coordination In The Gastroduodenal Areamentioning
confidence: 98%
“…In conscious pigs, pancreatic secretion exhibits a biphasic circadian pattern with a phase of basal secretion and a phase of meal-related enzyme-rich secretion. Basal pancreatic secretion is periodic and changes in parallel with duodenal motor activity (Abello et al 1988). Pancreatic secretion increases in both volume and enzyme concentration following food ingestion (Pierzynowski et al 1999).…”
Section: Discussionmentioning
confidence: 99%